The Effectiveness of Reciprocal Teaching Model on the Ecosystem Material - Negarani, Eryca Nur Bela; Yuniastuti, Ari; Iswari, Retno Sri (Journal of Biology Education, 2019)
Learning of reciprocal teaching model directing students to better understand the concepts and independent study. The purpose of this research is to analyze the effectiveness of reciprocal teaching model on ecosystem material to learning outcomes and conservation attitudes of high school students. The design of this research was quasi-experimental. The research population was all students of class X Sciences SMA Negeri 5 Magelang. Sampling was done by purposive sampling technique. The sample used is class X Sciences 2 (control class) and class X Sciences 3 (experimental class). Data collection techniques using observation, test, and questionnaires. Based on the results of the t test obtained the value of t count (4.249) > t table (2.068) which indicates that Ha is accepted. These results are supported by the results of students’ classical completeness of experimental class > 85% i.e. of 91.67% and the N-gain value of experimental class all students get value in the medium category compared to the control class there is one student in low category. Psychomotor learning outcomes of experimental class have higher average (79.98%) than the control class (75.34%). The results of conservation attitudes in experimental class > 75% of students get in good and very good categories in all observed conservation attitudes. The results of students’ responses showed 87.50% of students give responses in good and very good categories of reciprocal teaching model. The conclusion of this research is the use of reciprocal teaching model effective on ecosystem material to learning outcomes and conservation attitudes of students at SMA Negeri 5 Magelang.